Comparative quantitative assessment of global small bowel motility using magnetic resonance imaging in chronic intestinal pseudo‐obstruction and healthy controls. Issue 3 (10th December 2015) - Menys, A.; Butt, S.; Emmanuel, A.; Plumb, A. A.; Fikree, A.; Knowles, C.; Atkinson, D.; Zarate, N.; Halligan, S.; Taylor, S. A.
Abstract: Background: Chronic intestinal pseudo‐obstruction (CIPO) is characterized by dilatation of the bowel lumen and abnormal motility. In this study, we aimed to quantify small bowel dysmotility in CIPO using a validated pan‐intestinal motility assessment technique based on motion capture magnetic resonance imaging (MRI) compared to normal controls. In addition, we explored if motility responses of CIPO patients to neostigmine challenge differed from healthy volunteers. Methods: Twenty healthy volunteers (mean age 28, range 22–48) and 11 CIPO patients (mean age 47, range 19–90) underwent MRI enterography to capture global small bowel motility. Eleven controls and seven CIPO patients further underwent a randomized placebo‐controlled crossover study of either intravenous neostigmine (0.5 mg) or saline with motility MRI repeated at a mean of 3 weeks. Motility was quantified in regions of interest placed to encompass the whole small bowel volume using a validated, postprocessing technique to give a global motility index in arbitrary units (AU). Baseline and stimulated motility was compared using Wilcoxon rank–sum paired T ‐tests. Key Results: Baseline global small bowel motility was significantly lower in CIPO patients compared to controls (mean 0.25 AU vs 0.35 AU, p < 0.001). Motility in both groups increased significantly after neostigmine (0.06 AU increase, p = 0.016 in CIPO and 0.06 AU increase, p = 0.002 in controls). Three patients with scleroderma had a reduced response to neostigmine. Conclusions & Inferences: Global small bowel motility in CIPO patients is significantly lower than controls and response to the pro‐kinetic agent neostigmine may differ according to disease phenotype. Software‐quantified bowel motility using cine MRI has potential as a future tool to investigate enteric dysmotility. Abstract : The stimulatory effects of intravenous neostigmine on global small bowel motility may differ according to disease phenotype.